Understanding the building regulations - Polley, Simon (Milton Park, Abingdon, Oxon : Spon Press, 2012)
'Praise for previous editions:'Covers all the requirements of the Building Regulations as we know them today. It is clear and concise in its explanations ... A good book.' Clerk of Works Journal'A clear and concise introduction to the Building Regulations and Approved Documents ... Up-to-date {u2826} well presented and should benefit the student and any person wishing to find out about the Building Regulations and how to make an application to their Local Council.' ASI JournalDo you need a concise, jargon-free and compact guide to the UK building regulations? Simon Polley boils down the regulations to their basic features, explaining the core principles behind them. Easy to read and light enough to carry around with you, this is the ideal introduction to a vital part of your remit as a building control officer, architect or surveyor.Updated with the extensive 2010 changes, and illustrated with cartoons'--
'Well laid out, jargon-free and easy to use this practical guide is an excellent introduction for students as well as for professionals. This new edition sees full updates in line with the extensive 2010 changes to UK building regulations'--
Includes bibliographical references (p. [283]-287) and index.
Keywords: Building laws -- England; Building laws -- Wales